Digging Deeper : Evidence on the Effects of Macroprudential Policies from a New Database - Alam, Zohair (IMF Working Papers; Working Paper ;, 2019)
This paper introduces a new comprehensive database of macroprudential policies, which combines information from various sources and covers 134 countries from January 1990 to December 2016. Using these data, we first confirm that loan-targeted instruments have a significant impact on household credit, and a milder, dampening effect on consumption. Next, we exploit novel numerical information on loan-to-value (LTV) limits using a propensity-score-based method to address endogeneity concerns. The results point to economically significant and nonlinear effects, with a declining impact for larger tightening measures. Moreover, the initial LTV level appears to matter; when LTV limits are already tight, the effects of additional tightening on credit is dampened while those on consumption are strengthened.